ChemInform Abstract: Metal‐Catalyzed Activation of Ethers via C—O Bond Cleavage: A New Strategy for Molecular Diversity. Issue 6 (23rd January 2015) - Cornella, Josep; Zarate, Cayetana; Martin, Ruben
Abstract Review: [68 refs.